1997
DOI: 10.1515/zna-1997-0512
|View full text |Cite
|
Sign up to set email alerts
|

Internal Mobilities in the Molten Binary Systems (Tl, K)NO3 and (Tl, Cs)NO3

Abstract: Ratios of internal cation mobilities in the molten binary systems (Tl, K)NO a and (Tl, Cs)N0 3 have been measured by the Klemm method. From these and the data available on the densities and electric conductivities, the internal mobilities b have been calculated. While generally in the mixtures of T1N0 3 with alkali nitrates at constant temperature the conductivities and internal mobilities decrease with increasing molar volume, in (Tl, K)N0 3 they decrease with decreasing molar volume. This is explained by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In addition the sum of the angle between pharyngeal axis and the laryngeal axis and that between mouth axis and the pharyngeal axis was least in the sniffing position suggesting an advantage of the sniffing position over the simple head extension position. This study involved non anaesthetized volunteers and the laryngoscope blade was not used.Chow HC [12] further investigated the concepts of three axes and concluded that there is only involvement of two axes "oral and pharyngeal" and "the tongue". All these studies however pointed out that the angle between laryngeal axis and the line of vision was detected in sniffing as well as simple head extension position.…”
Section: Discussionmentioning
confidence: 99%
“…In addition the sum of the angle between pharyngeal axis and the laryngeal axis and that between mouth axis and the pharyngeal axis was least in the sniffing position suggesting an advantage of the sniffing position over the simple head extension position. This study involved non anaesthetized volunteers and the laryngoscope blade was not used.Chow HC [12] further investigated the concepts of three axes and concluded that there is only involvement of two axes "oral and pharyngeal" and "the tongue". All these studies however pointed out that the angle between laryngeal axis and the line of vision was detected in sniffing as well as simple head extension position.…”
Section: Discussionmentioning
confidence: 99%